2011
DOI: 10.4332/kjhpa.2011.21.4.565
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of untreated experiences among persons with physical disability

Abstract: Objective: This study is examined the factors affecting forms of untreated experiences in persons with physical disability.Method: The data collected from 461 persons with physical disability in community. Based on the Behavioral Model of Andersen, predisposing, enabling, and need factors are hypothesized to affect persons with physical disability's untreated experiences.The data were analyzed by statistical methods such as frequency and multiple logistic regression analysis.Result: Participation rates of untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…Both GR2 and GR3 had low levels of unmet healthcare needs caused by a lack of transportation and relatively high levels of unmet healthcare needs caused by an inconvenient reservation, waiting, or use time. In a previous study focused on the reasons for unmet healthcare needs, the most prevalent reason was found to be economic [27,30]. The fact that the reason for unmet healthcare needs varies according to the characteristics of the group and the level of inconvenience of transportation is the most likely explanation for why the current study found different results for the level of unmet healthcare needs in the rural elderly than previous studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Both GR2 and GR3 had low levels of unmet healthcare needs caused by a lack of transportation and relatively high levels of unmet healthcare needs caused by an inconvenient reservation, waiting, or use time. In a previous study focused on the reasons for unmet healthcare needs, the most prevalent reason was found to be economic [27,30]. The fact that the reason for unmet healthcare needs varies according to the characteristics of the group and the level of inconvenience of transportation is the most likely explanation for why the current study found different results for the level of unmet healthcare needs in the rural elderly than previous studies.…”
Section: Discussioncontrasting
confidence: 68%